Project risk management using Event Calculus - Gregoriades, Andreas; Lesta, Vicky Papadopoulou; Petrides, Petros (My University, 2011)
Risks are unavoidable in systems engineering projects due to emerging changes during the lifetime of projects. Changes in activities and peoples' roles are usually not free from conflicts, which in some cases if not dealt adequately, increase the project failure risks and could bring the whole project to a standstill. Herein, we present a method that examines the impact of change to project's duration which constitutes one of the most critical risks in project management. The method proposed utilizes two main criteria namely, the degree of dependency among activities and actors, and the temporal costs associated with the change. The proposed methodology is realised in Event Calculus (EC) and elaborated with an example.
Keywords: Conflict impact analysis; Event Calculus; Project risk managment; Impact analysis